A preliminary investigation of chitosan film as dressing for punch biopsy wounds in rats - Khan, TanveerAhmad; Peh, Khiang K. (Canadian Society for Pharmaceutical Sciences, 2003)

(untitled)
Purpose. To investigate the wound healing efficacy of two chitosan films, Chit-AA and Chit-LA, in comparison with a commercial preparation, Omiderm® using punch biopsy wounds in rats. Methods. The punch biopsy wounds were created in the abdominal region of male Wistar rats. The films were evaluated in terms of transparency, flexibility, adherence property, ease of removal from wounds without damaging underlying tissues and fluid accumulation. In addition, the wounds were examined for dryness, exudation, contraction, period of epithelialization and scar formation. Results. Chit-AA, Chit-LA and Omiderm® films were comparable in terms of transparency, flexibility, adherence property, ease of film removal from wounds without damaging underlying tissues and fluid accumulation. Although there was no statistically significant difference in wound dryness and exudation between the film treated wounds and untreated wounds (Control), a significant difference was obtained in complete wound closure (t100%), period of epithelialization and scar formation. Conclusions. Both Chit-LA and Chit-AA were able to promote wound healing with minimal scar formation.